The effects of oxygen-based disinfectant on dimensional accuracy of alginates - Muk, Y.P.; Mahmood, W.A.; Abu Kasim, N.H. (2005)
Objective: This study evaluated the effect of an active oxygen based disinfectant, 2 Perform® (Schulke & Mayr, Germany) on the dimensional accuracy of four alginates, Alginoplast (Heraeus Kulzer, Holland), Kromopan (LASCOD, Italy), Alginmax (MAJOR, Italy) and Duplast (Dentsply, China). Method: A cobalt chromium master model with four cylindrical studs representing 2 canines and 2 molars was constructed. A total of 40 impressions for each alginates were taken and treated in 4 different conditions, Immediate pour (control); 10 minutes immersion in distilled water; 10 minutes immersion in 2 Perform® and 30 minutes in 2 Perform®. The impressions were then poured in Type III stone. Dimensional changes between the master model and the resultant casts were measured using traveling microscope. The change at an antero-posterior dimension (C) and 3 different interarch dimensions (A,B and D) were noted. Results: Two way ANOVA showed significant interaction between alginates and treatment conditions except for dimension B and D. One-way ANOVA test and Student-Newman-Keuls indicated no significant difference (P> 0.05) in dimensional accuracy of impressions treated with Perform® for 10 minutes compared to the control group except for Alginoplast (dimension A) and Duplast (dimension C and D). The maximum deviation in the dimension after 10 minutes Perform® immersion was 0.552 for Duplast and 0.147 to 0.213 for other alginates. Immersion in Perform® for 30 minutes produced maximum deviation of 0.591 for Duplast in dimension C whilst 0.223 to 0.235 for other alginates. Conclusion: Active oxygen based disinfectant has an effect on the dimensional accuracy of the resultant cast for the 4 alginates. Although some results indicated significant change, the magnitude of deviation was clinically negligible. Apart from Duplast, all the alginates indicated good stability in 2 Perform® even up to 30 minutes of immersion time. (This study was supported by University of Malaya ; R&D FO200/2003D)